The Role of Public Notary in Providing Legal Protection on Standard Contracts for Indonesian Consumers - Deviana Yuanitasari (Faculty of Law, Sriwijaya University, Indonesia, 2017)
Public Notary is needed in conducting businesses of varying sectors. For example, people who want to own a house through a bank with House Ownership Loan (Kredit Pemilikan Rumah - KPR). Quite similar to a purchase of common loan contracts, the purchase of KPR contract is formulated into a standard contract. Its contents and clauses have been previously prepared by the bank. Then, bank customers as debtors only have the option to accept the entire contents and clauses of the KPR contract, otherwise they will not be granted KPR loan. As the consequence, the position of banks as lenders and customers as debtors are never equal. Debtors are powerless and have to comply with the content of the contract. This research discusses the protection given by notary in the drafting process of standard contract based on Law No 8 of 1999 on Consumer Protection (Undang-Undang Perlindungan Konsumen - UUPK) and Law No. 2 of 2014 on the Rules of Notary Profession (Undang-Undang Jabatan Notaris - UUJN). The result of the study showed that a public notary has a strong foundation to protect consumers’ rights according to the UUPK. An application of this, among others, the notary’s refusal has to include the entire content of the KPR agreement into a deed before s/he could examine whether the two parties of the agreement occupy an equal position and have proportionate power. For instance, in the transfer of responsibility clause from a bank as a business owner – a notary is entitled to advise the bank that its activity has violated the UUPK. If the bank insists that the clause is instructed by its central bank, the notary can help explain that the revision of the clause will help the Bank avoid the violation of UUPK.